2004
DOI: 10.1007/bf02946736
|View full text |Cite
|
Sign up to set email alerts
|

Method validation for the determination of ochratoxin A in green and soluble coffee by immunoaffinity column cleanup and liquid chromatography

Abstract: A method was validated for the determination of ochratoxin A (OTA) in soluble and green coffee. Performance parameters evaluated included selectivity, accuracy, intermediate precision, linearity, limit of detection, limit of quantitation, and ruggedness. The method was found to be selective for OTA in both matrices tested. Recovery rates from soluble coffee samples ranged from 73.5 to 91.2%, and from green coffee samples from 68.7 to 84.5%. The intermediate precision (RSDr) was between 9.1 and 9.4% for soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…The Limit of detection (LOD) of OTA was 1.2 ng.g -1 . The LOQ value was higher than that determined using other methods in the literature (VENTURA et al, 2003;DIAZ et al, 2004). The LOD value was lower than that reported by other authors using HPLC-FLD methods (FURLANI;SOARES, 1999;LEONI et al, 2001).…”
Section: Limit Of Quantification (Loq) and Limit Of Detection (Lod)contrasting
confidence: 63%
“…The Limit of detection (LOD) of OTA was 1.2 ng.g -1 . The LOQ value was higher than that determined using other methods in the literature (VENTURA et al, 2003;DIAZ et al, 2004). The LOD value was lower than that reported by other authors using HPLC-FLD methods (FURLANI;SOARES, 1999;LEONI et al, 2001).…”
Section: Limit Of Quantification (Loq) and Limit Of Detection (Lod)contrasting
confidence: 63%
“…In another study, green and processed coffee samples from Colombia were evaluated and OTA contamination were not detected in any sample analyzed (<1 ng/g) (Magnoli et al 2008). In contrast, Diaz et al (2004) found that green and processed coffee samples from Colombia were highly contaminated. The levels detected range from 0.90 to 19.40 ng/g and from 8.40 to 13.90 ng/g for green and processed coffee, respectively.…”
Section: Impact Of Ochratoxin a Production By Aspergillus Section Nigmentioning
confidence: 76%
“…An acceptable fit from the matrix-matched calibration curve showed a random pattern of residues in the working range (Figure 3), indicating a system free of bias confirming the method's linearity. 33 The value of Cochran's test was 0.58 (C calc ), lower than the value of 0.68 (C tab ) for the 5 levels of matrix-matches calibration curve with three replicates, proving the homoscedasticity. Figure 4 shows a chromatogram of spiked roasted coffee in 3.0 ng g -1 and an example for blank roasted coffee.…”
Section: Linearitymentioning
confidence: 81%
“…Coelution problem of interfering compounds and retention time shifts could lead to erroneous positive or negative results can be overcome by structural elucidation provided by coupling of LC and mass spectrometry (MS). 33 In general, and no matters the applied detection technique, there is a need for a careful sample clean up. The extract is usually purified by solid-phase extraction, or by using immunoaffinity absorbent materials, or by a combination of both.…”
Section: Introductionmentioning
confidence: 99%